2021
DOI: 10.3390/pathogens10111494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of SARS-CoV-2 Infection among Parturients and Newborns from Luanda, Angola

Abstract: SARS-CoV-2 emerged in China in December 2019, creating a massive public health concern. Although previous studies have identified SARS-CoV-2 in pregnant women, the possibility of transmission to newborns remains uncertain. Herein, we investigated SARS-CoV-2 infection and risk factors among parturients and newborns. This was a cross-sectional study carried out with 3633 parturients from Luanda, Angola, between January and April 2021, with an age ranging from 13 to 48 years. SARS-CoV-2 infection of the parturien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…The high rate of adherence to vaccines against SARS‐CoV‐2 observed in this population in Angola, might be a reflection of the success of the strategies such as (i) information in different media and (ii) awareness campaigns adopted by the Angolan Ministry of Health, as measures to reduce the spread and mortality of COVID‐19 in the Angolan population. These measures also showed positive results in the spread of SARS‐CoV‐2 infection in low prevalence among the Angolan population residing in different settings, as reported by our research team in previous studies 13–17 . A cohort study carried out in Italy, found that about 88% of the population was fully vaccinated which was slightly low compared with the 98% rate of vaccinates observed in our study (Table 1).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high rate of adherence to vaccines against SARS‐CoV‐2 observed in this population in Angola, might be a reflection of the success of the strategies such as (i) information in different media and (ii) awareness campaigns adopted by the Angolan Ministry of Health, as measures to reduce the spread and mortality of COVID‐19 in the Angolan population. These measures also showed positive results in the spread of SARS‐CoV‐2 infection in low prevalence among the Angolan population residing in different settings, as reported by our research team in previous studies 13–17 . A cohort study carried out in Italy, found that about 88% of the population was fully vaccinated which was slightly low compared with the 98% rate of vaccinates observed in our study (Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…These measures also showed positive results in the spread of SARS-CoV-2 infection in low prevalence among the Angolan population residing in different settings, as reported by our research team in previous studies. [13][14][15][16][17] A cohort study carried out in Italy, found that about 88% of the population was fully vaccinated which was slightly low compared with the 98% rate of vaccinates observed in our study (Table 1). Also, our study presents about 10% of the unvaccinated population and there were mainly non-healthcare professionals,…”
Section: Discussioncontrasting
confidence: 68%
“… 19 Another study conducted in parturient women from Angola between January and April 2021, found a prevalence of 0.4% of SARS-CoV-2 infection using a rapid antigenic testing and RT-PCR. 33 By contrast, a study conducted in Kenyan pregnant women from May 2020 to February 2021 reported a prevalence of 31% of clinical COVID-19. 34 However, none of these studies provided seroprevalence data, making it difficult to compare their results with this study.…”
Section: Discussionmentioning
confidence: 95%